Exploiting the porin pathway for polar compound delivery into Gram-negative bacteria. (June 2016) - Scorciapino, Mariano Andrea; D'Agostino, Tommaso; Acosta-Gutierrez, Silvia; Malloci, Giuliano; Bodrenko, Igor; Ceccarelli, Matteo
Background: In Gram-negative bacteria, the outer-membrane represents an additional barrier for antibiotics to permeate inside pathogens. Our inability to come up with novel effective antibiotics mostly relies upon insufficient understanding of the molecular basis behind outer-membrane penetration.Results: Polar antibiotics can permeate through water-filled porins, such as OmpF and OmpC from Escherichia coli . Through molecular modeling, permeation of imipenem and meropenem was found to be strongly dependent upon capability of drugs to properly align their electric dipole to the internal electric field in the restricted region of the pore. Electrostatics differences between OmpF and OmpC, and modifications along a series of OmpC mutants from E. coli -resistant clinical strains identify a 'preorientation' region, which dramatically affects antibiotic pathway.Conclusion: A novel perspective is presented, suggesting new molecular properties to be included in drug design.